Low-voltage distribution network commutation method, commutation device and terminal - LI XINMEI; WANG HUIHAI; DING JIAFENG; LIANG XIAO; YIN LINZI; GONG FEI; LIU JING (2018)
The invention discloses a low-voltage distribution network commutation method, a commutation device and a terminal. The method comprises: step one, a current zero-crossing time is obtained and a currently connected phase sequence is cut off based on the current zero-crossing time; step two, primary checking for checking whether the phase sequence in the step one is cut off successfully is carriedout at a first checking time T3; if the primary checking is done successfully, step three is performed and otherwise, the step one is performed; step three, a second checking time T5 is obtained and voltage zero-crossing detection is carried out synchronously, and whether secondary checking and new phase sequence cutting are carried out is determined based on a result of detection of a voltage zero-crossing point before arrival of the second checking time T5; and step four, checking of successful cutting of the new phase sequence is carried out at a third checking time T7; if checking is donesuccessfully, the new phas